Cyclosporin and mitochondria: a neuroprotective approach - Singh, Alok; Khare, Vivek (International Journal of Basic & Clinical Pharmacology, 2017)
Cyclosporin A (CsA) an immunophilin, discovered in 1969 and approved in 1983 to be used as immunosuppressant agent and is widely used in organ transplantation and auto-immune disorders. Its ability to alter mitochondria and apoptotic pathways makes it attractive agent to be employed in variety of diseases including age related neurodegenerative diseases. Mitochondria play pivotal role in cell energetics and reactive oxygen species production and are known to be key regulator of apoptosis hence it is important in a wide range of diseases. The structural and functional properties of mitochondria enable the targeting of drugs supposed to modulate the function of organelle for therapeutic advantage. By targeting mitochondria we can prevent oxidative damage associated with neurodegenerative diseases and ischemia and reperfusion tissue injury. Similarly targeting Bcl-2 can be helpful in cancer by triggering apoptosis.